Wear-resistant engineering plastic master batch and preparation method thereof

The wear-resistant engineering plastic masterbatch, prepared with specific components and processes, addresses uneven dispersion and poor compatibility issues, achieving improved mechanical properties and long-term stability.

CN119192830APending Publication Date: 2024-12-27LANGFANG GONGXING PLASTIC PROD CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411596183.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional engineering plastic masterbatches suffer from uneven filler dispersion, poor compatibility between components, and lack of anti-aging properties, leading to decreased mechanical properties and service life due to issues like filler stratification and poor thermal stability.

Method used

A wear-resistant engineering plastic masterbatch composed of modified polyethylene, polytetrafluoroethylene powder, graphite powder, silane coupling agent, epoxy resin, nano-alumina, antioxidant, and ultraviolet absorber, with a specific mass percentage ratio, is prepared through degassing, surface modification, and composite extrusion to ensure uniform distribution and bonding, followed by antistatic coating.

Benefits of technology

The masterbatch exhibits enhanced wear resistance, anti-aging ability, and stability under high friction and load, with improved component bonding and uniform dispersibility, extending the service life and reliability of engineering components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192830A_ABST
    Figure CN119192830A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of engineering plastic preparation, in particular to a wear-resistant engineering plastic master batch and a preparation method thereof.The preparation method comprises the following steps that S1, polyamide resin is subjected to degassing treatment in a vacuum environment; s2, performing surface pretreatment on nano aluminum oxide and a silane coupling agent; s3, mixing the polyamide resin, the polytetrafluoroethylene powder, the nano aluminum oxide, the modified polyethylene and the graphite micro powder to form a mixture A; s4, sequentially adding the epoxy resin, the antioxidant and the ultraviolet light absorber to form a mixture B; s5, carrying out composite extrusion to form a master batch matrix; and S6, carrying out cooling granulation treatment on the extruded master batch matrix, and carrying out antistatic coating treatment on the surface of the master batch to obtain a final wear-resistant engineering plastic master batch finished product. According to the invention, through uniform dispersion of multiple components and enhancement of binding force, high wear resistance, aging resistance and storage and transportation stability are realized, and the service life of the material in a severe environment is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engineering plastic preparation, in particular to a wear-resistant engineering plastic masterbatch and a preparation method thereof. Background Art

[0002] In modern industrial and engineering applications, engineering plastic masterbatches are widely used to manufacture high-strength, wear-resistant parts such as gears, bearings and sliding parts to meet the high requirements of material wear resistance, impact resistance and thermal stability in mechanical processing, automobile, aviation and other fields.

[0003] Traditional engineering plastic masterbatches usually rely on a single modifier or filler to improve wear resistance. However, in actual use, these masterbatches often suffer from decreased mechanical properties and service life due to problems such as uneven filler dispersion, poor compatibility between components, and lack of anti-aging properties. In addition, due to the limited binding force of various components in the masterbatch matrix, they are prone to falling off or stratification during processing and long-term use, making it difficult to achieve high wear resistance and long-term stability.

[0004] Therefore, in order to solve the problems of insufficient wear resistance, uneven dispersion and poor thermal stability of masterbatches in the prior art, there is an urgent need for a wear-resistant engineering plastic masterbatch and a preparation method thereof to solve the above problems. Summary of the invention

[0005] Based on the above purpose, the present invention provides a wear-resistant engineering plastic masterbatch and a preparation method thereof.

[0006] A wear-resistant engineering plastic masterbatch, comprising modified polyethylene, polytetrafluoroethylene powder, graphite powder, silane coupling agent, epoxy resin, nano-alumina, antioxidant, ultraviolet absorber and polyamide resin; wherein the mass percentage of each component is: Modified polyethylene: 10%-15%; Polytetrafluoroethylene powder: 5%-10%; Graphite powder: 2%-5%; Silane coupling agent: 1%-3%; Epoxy resin: 5%-10%; Nano-alumina: 15%-20%; Antioxidants: 0.3%-0.8%; UV absorber: 0.2%-0.7%; The balance is polyamide resin.

[0007] Optionally, the particle size of the graphite powder is 0.5-5 microns; the polyamide resin is selected from nylon 6 or nylon 66; the silane coupling agent is selected from vinyl trimethoxy silane or acryloxypropyl trimethoxy silane; and the particle size of the polytetrafluoroethylene powder is 1-10 microns.

[0008] Optionally, the modified polyethylene is a blend of high-density polyethylene and low-density polyethylene, wherein the ratio of high-density polyethylene to low-density polyethylene is 2:1.

[0009] A method for preparing a wear-resistant engineering plastic masterbatch comprises the following steps: S1: firstly degas the polyamide resin in a vacuum environment to remove moisture and impurities inside the polyamide resin; S2: pre-treating the surface of nano-alumina with a silane coupling agent to form an active layer; S3: adding the degassed polyamide resin, polytetrafluoroethylene powder, pretreated nano-alumina, modified polyethylene and graphite powder into a mixing device for preliminary mixing to form a mixture A; S4: gradually increasing the temperature of the mixing equipment, and sequentially adding the epoxy resin, the antioxidant and the ultraviolet absorber, and mixing them thoroughly to form a mixture B; S5: Compounding and extruding the mixture B through an extrusion device to form a masterbatch matrix with a dense structure; S6: Cooling and granulating the extruded masterbatch matrix, and performing antistatic coating treatment on the surface of the masterbatch to obtain the final wear-resistant engineering plastic masterbatch finished product.

[0010] Optionally, the S1 specifically includes: S11: placing the polyamide resin in a vacuum drying oven, heating it to 80-100° C., and maintaining a constant temperature to preheat the polyamide resin; S12: Under constant temperature conditions, the pressure of the vacuum drying oven is gradually reduced to 0.05-0.1 MPa, and vacuum extraction of the polyamide resin is started to reduce the moisture content; S13: Maintain constant temperature treatment under vacuum for 30-60 minutes; S14: gradually restore the pressure of the vacuum drying oven to normal pressure and simultaneously lower the temperature to room temperature.

[0011] Optionally, the S2 specifically includes: S21: mixing a silane coupling agent and ethanol in a mass ratio of 1:20-1:30, and stirring evenly to prepare a coupling agent solution; S22: adding nano-alumina to the coupling agent solution, and performing ultrasonic dispersion at an ultrasonic frequency of 20-40 kHz for 10-20 minutes; S23: heating the uniformly dispersed mixture at 60-80° C. and stirring the mixture for 30-60 minutes to allow the coupling agent to bond with the surface of the nano-alumina; S24: After the reaction is completed, the mixture is filtered, the treated nano-alumina is collected, and dried at 70-90° C. to constant weight.

[0012] Optionally, the S3 specifically includes: S31: adding the degassed polyamide resin into a mixing device and heating it to 100-120° C. to maintain the fluidity of the polyamide resin; S32: while the polyamide resin is kept in a fluid state, polytetrafluoroethylene powder, pretreated nano-alumina and graphite powder are added in sequence to uniformly disperse the fillers; S33: After the filler is dispersed, the modified polyethylene is added and stirring is continued; S34: Raise the temperature of the mixing equipment to 120-140° C. and mix at a stirring speed of 200-300 rpm for 5-10 minutes until a uniform mixture A is formed.

[0013] Optionally, the S4 specifically includes: S41: gradually raising the temperature of the mixing device to 150° C., maintaining the stirring state, and ensuring that the previously formed mixture A is in a uniform flow state; S42: slowly adding epoxy resin into mixture A at 150° C. and continuously stirring for 5-8 minutes; S43: After the mixture is uniformly mixed, the temperature is further increased to 170° C.; S44: adding an antioxidant and a UV absorber at 170° C. and continuing stirring for 3-5 minutes to finally form a uniform mixture B.

[0014] Optionally, the S5 specifically includes: S51: preheating the temperature of the extrusion equipment to 170-190°C; S52: slowly adding the mixture B to the feeding port of the extruder, and controlling the feeding speed to 2-5 kg / hour; S53: performing composite extrusion treatment on the mixture B under the condition that the screw speed is set to 60-100 rpm; S54: During the extrusion process, the pressure in the extrusion equipment is controlled to be 5-8 MPa; S55: Cooling the extruded masterbatch matrix to 50-70° C. through a cooling device to stabilize its structural density and form a masterbatch matrix with a dense structure.

[0015] Optionally, the S6 specifically includes: S61: The extruded masterbatch matrix is ​​treated in a cooling water bath to be cooled to 30-50° C., so that the masterbatch matrix reaches a Shore hardness of D40-60; S62: sending the cooled masterbatch matrix into a pelletizer and cutting it into granules at a speed of 500-1000 kg / hour to obtain preliminary masterbatch after cooling and granulation; S63: dissolving the antistatic agent in ethanol or deionized water to prepare an antistatic coating solution with a mass concentration of 0.5%-2%, and stirring the solution evenly; S64: placing the preliminary masterbatch in a drum coating device, and spraying the antistatic coating solution evenly on the surface of the masterbatch in a rolling state; S65: Drying the masterbatch sprayed with the antistatic coating at 50-70° C. to a constant weight to form a final wear-resistant engineering plastic masterbatch product.

[0016] Beneficial effects of the present invention: The present invention significantly improves the uniform dispersibility and bonding strength of each component through the optimized ratio of multiple modified components and scientific preparation process, so that the masterbatch has excellent wear resistance in high friction and high load application environments. In particular, the stable distribution of components such as nano-alumina, graphite powder, and polytetrafluoroethylene powder in the matrix effectively prevents performance degradation caused by delamination or shedding.

[0017] The present invention introduces antioxidants and ultraviolet absorbers, so that the masterbatch has good anti-aging ability in long-term use and can maintain stable mechanical properties in high temperature and outdoor environments.

[0018] The present invention ensures the deep combination of various components through the steps of degassing pretreatment, surface modification, composite extrusion, etc., and further improves the stability of the masterbatch during storage and transportation by using antistatic coating treatment. This high-performance wear-resistant engineering plastic masterbatch not only effectively extends the service life of engineering components, but also exhibits excellent reliability and durability in harsh industrial application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 This is a schematic diagram of the components of the wear-resistant engineering plastic masterbatch according to an embodiment of the present invention; Figure 2 Schematic diagram of a method for preparing wear-resistant engineering plastic masterbatch according to an embodiment of the present invention. DETAILED DESCRIPTION

[0021] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternatives to implement some known technologies; and the accompanying drawings are only for more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0022] It should be noted that the references to "one embodiment", "embodiment", "exemplary embodiments", "some embodiments" and the like in the specification indicate that the embodiments described may include specific features, structures or characteristics, but not every embodiment may include the specific features, structures or characteristics. In addition, when a specific feature, structure or characteristic is described in conjunction with an embodiment, it should be within the knowledge of a person skilled in the art to implement such feature, structure or characteristic in conjunction with other embodiments (whether or not explicitly described).

[0023] In general, a term can be understood, at least in part, from its use in context. For example, depending, at least in part, on the context, the term "one or more" as used herein can be used to describe any feature, structure, or characteristic in the singular sense, or can be used to describe a combination of features, structures, or characteristics in the plural sense. Additionally, the term "based on" can be understood as not necessarily intended to convey an exclusive set of factors, but can instead, depending, at least in part, on the context, allow for the presence of other factors that are not necessarily explicitly described.

[0024] Example 1 like Figure 1 As shown, a wear-resistant engineering plastic masterbatch includes modified polyethylene, polytetrafluoroethylene powder, graphite powder, silane coupling agent, epoxy resin, nano-alumina, antioxidant, ultraviolet absorber and polyamide resin; wherein the mass percentage of each component is: Modified polyethylene 13%; Polytetrafluoroethylene powder 7%; Graphite powder 4%; Silane coupling agent 2%; Epoxy resin 7%; Nano-alumina 17%; Antioxidant 0.5%; UV absorber 0.5%; The balance is polyamide resin.

[0025] The particle size of graphite powder is 3 microns; the polyamide resin is selected from nylon 6; the silane coupling agent is selected from vinyl trimethoxy silane; and the particle size of polytetrafluoroethylene powder is 5 microns.

[0026] The modified polyethylene is a blend of high-density polyethylene and low-density polyethylene, wherein the ratio of high-density polyethylene to low-density polyethylene is 2:1.

[0027] like Figure 2 As shown, a method for preparing a wear-resistant engineering plastic masterbatch comprises the following steps: S1: First, the polyamide resin is degassed in a vacuum environment to remove moisture and impurities inside it and improve its compatibility with other components; S2: pre-treating the surface of nano-alumina with silane coupling agent to form an active layer to enhance its dispersibility and bonding ability in the masterbatch matrix; S3: adding the degassed polyamide resin, polytetrafluoroethylene powder, pretreated nano-alumina, modified polyethylene and graphite powder into a mixing device for preliminary mixing to form a mixture A; S4: gradually increase the temperature of the mixing equipment, and add the epoxy resin, antioxidant and ultraviolet absorber in sequence, and mix them thoroughly to form a mixture B to ensure that each additive is evenly distributed in the masterbatch matrix; S5: Compounding and extruding the mixture B through an extrusion device to form a masterbatch matrix with a dense structure; S6: Cooling and granulating the extruded masterbatch matrix, and performing antistatic coating treatment on the surface of the masterbatch to obtain the final wear-resistant engineering plastic masterbatch finished product.

[0028] S1 specifically includes: S11: placing the polyamide resin in a vacuum drying oven, heating it to 90° C., and maintaining a constant temperature to preheat the polyamide resin; S12: Under constant temperature conditions, the pressure of the vacuum drying oven is gradually reduced to 0.08 MPa, and vacuum extraction of the polyamide resin is started to reduce the moisture content; S13: Maintaining constant temperature treatment under vacuum for 40 minutes to further remove moisture and impurities in the polyamide resin; S14: gradually restore the pressure of the vacuum drying oven to normal pressure, and at the same time reduce the temperature to room temperature to complete the degassing treatment of the polyamide resin.

[0029] S2 specifically includes: S21: mixing a silane coupling agent and ethanol in a mass ratio of 1:25, and stirring evenly to prepare a coupling agent solution; S22: adding nano-alumina to the coupling agent solution and performing ultrasonic dispersion at an ultrasonic frequency of 30 kHz for 15 minutes to ensure uniform dispersion; S23: heating the uniformly dispersed mixture at 70° C. and stirring the mixture for 40 minutes to allow the coupling agent to bond with the surface of the nano-alumina; S24: After the reaction is completed, the mixture is filtered, the treated nano-alumina is collected, and dried at 80° C. to constant weight, thereby completing the surface pretreatment.

[0030] S3 specifically includes: S31: adding the degassed polyamide resin into a mixing device and heating it to 110° C. to maintain the fluidity of the polyamide resin; S32: while the polyamide resin is kept in a fluid state, polytetrafluoroethylene powder, pretreated nano-alumina and graphite powder are added in sequence to uniformly disperse the fillers; S33: After the filler is dispersed, the modified polyethylene is added and stirred continuously to fully mix the modified polyethylene with the matrix and the filler; S34: The temperature of the mixing device was raised to 130° C., and the mixture was mixed at a stirring speed of 250 rpm for 7 minutes until a uniform mixture A was formed.

[0031] S4 specifically includes: S41: gradually raising the temperature of the mixing device to 150° C., maintaining the stirring state, and ensuring that the previously formed mixture A is in a uniform flow state; S42: slowly adding the epoxy resin into the mixture A at 150° C. and continuously stirring for 7 minutes to ensure sufficient contact between the epoxy resin and the mixture A; S43: After the mixture is uniformly mixed, the temperature is further increased to 170° C.; S44: At 170° C., antioxidant and ultraviolet absorber were added and stirred for 4 minutes to make them evenly distributed in the mixture, and finally a uniform mixture B was formed.

[0032] S5 specifically includes: S51: Preheat the temperature of the extrusion equipment to 180°C to ensure uniform temperature inside the equipment; S52: slowly adding the mixture B to the feeding port of the extruder, and controlling the feeding speed at 3 kg / hour so that the mixture B evenly enters the extrusion screw; S53: Under the condition that the screw speed is set to 80 rpm, the mixture B is subjected to a composite extrusion process to ensure that the components are evenly distributed and tightly combined under the action of shear force; S54: During the extrusion process, the pressure in the extrusion device is controlled to be 6 MPa to further densify the structure of the masterbatch matrix; S55: The extruded masterbatch matrix is ​​cooled to 60° C. by a cooling device to stabilize its structural density and form a masterbatch matrix with a dense structure, ready for the subsequent granulation process.

[0033] S6 specifically includes: S61: The extruded masterbatch matrix is ​​treated in a cooling water bath and cooled to 40° C. so that the masterbatch matrix reaches a Shore hardness of D50; S62: sending the cooled masterbatch matrix into a pelletizer and cutting it into granules at a speed of 700 kg / hour to obtain preliminary masterbatch after cooling and granulation; S63: dissolving the antistatic agent in ethanol to prepare an antistatic coating solution with a mass concentration of 1%, and stirring the solution evenly; S64: placing the preliminary masterbatch in a drum coating device, and spraying the antistatic coating solution evenly on the surface of the masterbatch in a rolling state, so that the coating completely covers the masterbatch; S65: Drying the masterbatch sprayed with the antistatic coating at 60° C. to a constant weight to form a final wear-resistant engineering plastic masterbatch product.

[0034] Example 2 Material ratio: modified polyethylene 10%; polytetrafluoroethylene powder (particle size is 1 micron) 5%; graphite powder (particle size is 0.5 micron) 2%; silane coupling agent (acryloxypropyltrimethoxysilane) 1%; epoxy resin 5%; nano alumina 15%; antioxidant 0.3%; ultraviolet absorber 0.2%; the balance is polyamide resin (nylon 66).

[0035] The preparation steps are as follows: S1: First, place the polyamide resin in a vacuum drying oven, heat it to 80°C and keep the temperature constant, gradually reduce the pressure in the vacuum drying oven to 0.05MPa, so as to effectively remove moisture and impurities in the polyamide resin, and maintain the constant temperature treatment at this pressure for 30 minutes to ensure that the polyamide resin is fully degassed before use; S2: Mix the silane coupling agent and ethanol in a mass ratio of 1:20 and stir evenly to prepare a coupling agent solution, then add the nano-alumina to the coupling agent solution and perform ultrasonic dispersion at an ultrasonic frequency of 20 kHz for 10 minutes; then, heat the evenly dispersed mixture to 60°C and stir the reaction at this temperature for 30 minutes to promote the bonding between the coupling agent and the surface of the nano-alumina. After the reaction is completed, filter the mixture and collect the treated nano-alumina, and finally dry it at 70°C to constant weight; S3: adding the degassed polyamide resin into a mixing device and heating it to 100° C. to maintain its fluidity, adding polytetrafluoroethylene powder, pretreated nano-alumina and graphite powder in sequence while the polyamide resin remains in a fluid state, stirring to ensure that the fillers are evenly dispersed, then adding modified polyethylene and raising the temperature of the mixing device to 120° C., mixing at a stirring speed of 200 rpm for 5 minutes until a uniform mixture A is formed; S4: gradually increase the temperature of the mixing equipment to 150°C, keep stirring to ensure that the mixture A is in a uniform flow state, slowly add the epoxy resin at 150°C and continue stirring for 5 minutes, then continue to increase the temperature to 170°C, add the antioxidant and the ultraviolet absorber in sequence at 170°C, and continue stirring for 3 minutes to form a uniform mixture B; S5: preheating the extrusion equipment to 170°C, and slowly adding the mixture B into the feeding port of the extrusion equipment, controlling the feeding speed to 2kg / hour, and performing a composite extrusion process on the mixture B under the condition that the screw speed is set to 60 rpm, while controlling the pressure in the extrusion equipment to 5MPa, and cooling the extruded masterbatch matrix to 50°C through a cooling device to form a masterbatch matrix with a dense structure; S6: The extruded masterbatch matrix is ​​treated in a cooling water bath and cooled to 30°C to reach a Shore hardness of D40; then, the cooled masterbatch matrix is ​​sent to a pelletizer and cut into granules at a speed of 500kg / hour to obtain a preliminary masterbatch. Next, the antistatic agent is dissolved in deionized water to prepare an antistatic coating solution with a mass concentration of 0.5%, and the solution is fully stirred. The preliminary masterbatch is placed in a drum coating device, and the antistatic coating solution is evenly sprayed in a rolling state. Finally, it is dried at 50°C to constant weight to obtain the final wear-resistant engineering plastic masterbatch product.

[0036] Example 3 Material ratio: modified polyethylene 15%; polytetrafluoroethylene powder (particle size is 10 microns) 10%; graphite powder (particle size is 5 microns) 5%; silane coupling agent (vinyl trimethoxy silane) 3%; epoxy resin 10%; nano alumina 20%; antioxidant 0.8%; ultraviolet absorber 0.7%; the balance is polyamide resin (nylon 6).

[0037] The preparation steps are as follows: S1: First, place the polyamide resin in a vacuum drying oven, heat it to 100°C and keep it at a constant temperature, gradually reduce the pressure in the vacuum drying oven to 0.1MPa, so as to effectively remove moisture and impurities in the polyamide resin, and maintain the constant temperature treatment at this pressure for 60 minutes to ensure that the polyamide resin is fully degassed before use; S2: Mix the silane coupling agent and ethanol in a mass ratio of 1:30 and stir evenly to prepare a coupling agent solution, then add the nano-alumina to the coupling agent solution and perform ultrasonic dispersion at an ultrasonic frequency of 40 kHz for 20 minutes; then, heat the evenly dispersed mixture to 80°C and stir the reaction at this temperature for 60 minutes to promote the bonding between the coupling agent and the surface of the nano-alumina. After the reaction is completed, filter the mixture and collect the treated nano-alumina, and finally dry it at 90°C to constant weight; S3: adding the degassed polyamide resin into a mixing device and heating it to 120° C. to maintain its fluidity, adding polytetrafluoroethylene powder, pretreated nano-alumina and graphite powder in sequence while the polyamide resin remains in a fluid state, stirring to ensure that the fillers are evenly dispersed, then adding modified polyethylene and raising the temperature of the mixing device to 140° C., mixing at a stirring speed of 300 rpm for 10 minutes, until a uniform mixture A is formed; S4: gradually increase the temperature of the mixing equipment to 150°C, keep stirring to ensure that the mixture A is in a uniform flow state, slowly add the epoxy resin at 150°C and continue stirring for 8 minutes, then continue to increase the temperature to 170°C, add the antioxidant and the ultraviolet absorber in sequence at 170°C, and continue stirring for 5 minutes to form a uniform mixture B; S5: preheating the extrusion equipment to 190°C, and slowly adding the mixture B into the feeding port of the extrusion equipment, controlling the feeding speed to 5kg / hour, and performing a composite extrusion process on the mixture B under the condition that the screw speed is set to 100 rpm, while controlling the pressure in the extrusion equipment to 8MPa, and cooling the extruded masterbatch matrix to 70°C through a cooling device to form a masterbatch matrix with a dense structure; S6: The extruded masterbatch matrix is ​​treated in a cooling water bath and cooled to 50°C to reach a Shore hardness of D60; then, the cooled masterbatch matrix is ​​sent to a pelletizer and cut into particles at a speed of 1000kg / hour to obtain a preliminary masterbatch. Next, the antistatic agent is dissolved in ethanol to prepare an antistatic coating solution with a mass concentration of 2%, and the solution is fully stirred. The preliminary masterbatch is placed in a drum coating device, and the antistatic coating solution is evenly sprayed in a rolling state. Finally, it is dried at 70°C to constant weight to obtain the final wear-resistant engineering plastic masterbatch product.

[0038] Table 1 Comparison of performance parameters of finished products of wear-resistant engineering plastic masterbatch Performance Indicators Example 1 Example 2 Example 3 Wear resistance (mg / 1000 revolutions) 0.5 1 0.8 Antioxidant properties (h) 1200 900 1000 UV resistance (h) 1000 800 900 Antistatic effect (Ω·cm) 1E+12 5E+11 8E+11 Hardness (Shore D) 50 40 60 Tensile strength (MPa) 80 70 75 Impact strength (kJ / m²) 25 18 22 As can be seen from Table 1 above, Example 1 performs best in terms of wear resistance, oxidation resistance, UV resistance and antistatic effect, and its tensile strength and impact strength also reach a high level, and the hardness is moderate (Shore hardness D50), and it performs well in multiple performance indicators. In contrast, Examples 2 and 3 are lacking in some performances, such as slightly lower values ​​of wear resistance, UV resistance and antistatic effect. Therefore, Example 1 is considered to be the best implementation scheme, suitable for engineering plastic application scenarios that require high wear resistance and excellent anti-aging performance.

[0039] Table 2 Comparison of other performance parameters Performance Indicators Example 1 Example 2 Example 3 Thermal stability (°C) 280 260 270 Corrosion resistance (% mass loss) 0.2 0.5 0.3 Water absorption (%) 0.05 0.15 0.1 Density (g / cm³) 1.15 1.1 1.13 Thermal conductivity (W / m·K) 0.45 0.4 0.42 Dielectric constant 2.5 2 2.3 Friction coefficient 0.12 0.2 0.15 It can be seen from Table 2 above that Example 1 performs best in terms of thermal stability, corrosion resistance, water absorption and thermal conductivity. Its higher thermal stability (280°C) and lower water absorption (0.05%) enable it to have stronger reliability in high temperature and humid environments. At the same time, the thermal conductivity (0.45 W / m·K) and lower friction coefficient (0.12) of Example 1 also provide it with good thermal conductivity and wear resistance in engineering applications. These characteristics make Example 1 the best choice for wear-resistant engineering plastics, and are particularly suitable for application scenarios with higher requirements for high temperature resistance, low water absorption and high corrosion resistance.

[0040] The present invention covers any substitution, modification, equivalent method and scheme made on the essence and scope of the present invention. In order to make the public have a thorough understanding of the present invention, specific details are described in detail in the following preferred embodiments of the present invention, but those skilled in the art can fully understand the present invention without the description of these details. In addition, in order to avoid unnecessary confusion about the essence of the present invention, well-known methods, processes, procedures, components and circuits are not described in detail.

[0041] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A wear-resistant engineering plastic masterbatch, characterized in that: It includes modified polyethylene, polytetrafluoroethylene powder, graphite powder, silane coupling agent, epoxy resin, nano-alumina, antioxidant, ultraviolet absorber and polyamide resin; wherein the mass percentage of each component is: Modified polyethylene: 10%-15%; Polytetrafluoroethylene powder: 5%-10%; Graphite powder: 2%-5%; Silane coupling agent: 1%-3%; Epoxy resin: 5%-10%; Nano-alumina: 15%-20%; Antioxidants: 0.3%-0.8%; UV absorber: 0.2%-0.7%; The balance is polyamide resin.

2. The wear-resistant engineering plastic masterbatch according to claim 1, characterized in that: The particle size of the graphite powder is 0.5-5 microns; the polyamide resin is selected from nylon 6 or nylon 66; the silane coupling agent is selected from vinyl trimethoxy silane or acryloxypropyl trimethoxy silane; and the particle size of the polytetrafluoroethylene powder is 1-10 microns.

3. The wear-resistant engineering plastic masterbatch according to claim 1, characterized in that: The modified polyethylene is a blend of high-density polyethylene and low-density polyethylene, wherein the ratio of high-density polyethylene to low-density polyethylene is 2:

1.

4. A method for preparing a wear-resistant engineering plastic masterbatch according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: firstly degas the polyamide resin in a vacuum environment to remove moisture and impurities inside the polyamide resin; S2: pre-treating the surface of nano-alumina with a silane coupling agent to form an active layer; S3: adding the degassed polyamide resin, polytetrafluoroethylene powder, pretreated nano-alumina, modified polyethylene and graphite powder into a mixing device for preliminary mixing to form a mixture A; S4: gradually increasing the temperature of the mixing equipment, and sequentially adding the epoxy resin, the antioxidant and the ultraviolet absorber, and mixing them thoroughly to form a mixture B; S5: Compounding and extruding the mixture B through an extrusion device to form a masterbatch matrix with a dense structure; S6: Cooling and granulating the extruded masterbatch matrix, and performing antistatic coating treatment on the surface of the masterbatch to obtain the final wear-resistant engineering plastic masterbatch finished product.

5. The method for preparing a wear-resistant engineering plastic masterbatch according to claim 4, characterized in that: The S1 specifically includes: S11: placing the polyamide resin in a vacuum drying oven, heating it to 80-100° C., and maintaining a constant temperature to preheat the polyamide resin; S12: Under constant temperature conditions, the pressure of the vacuum drying oven is gradually reduced to 0.05-0.1 MPa, and vacuum extraction of the polyamide resin is started to reduce the moisture content; S13: Maintain constant temperature treatment under vacuum for 30-60 minutes; S14: gradually restore the pressure of the vacuum drying oven to normal pressure and simultaneously lower the temperature to room temperature.

6. The method for preparing a wear-resistant engineering plastic masterbatch according to claim 4, characterized in that: The S2 specifically includes: S21: mixing a silane coupling agent and ethanol in a mass ratio of 1:20-1:30, and stirring evenly to prepare a coupling agent solution; S22: adding nano-alumina to the coupling agent solution, and performing ultrasonic dispersion at an ultrasonic frequency of 20-40 kHz for 10-20 minutes; S23: heating the uniformly dispersed mixture at 60-80° C. and stirring the mixture for 30-60 minutes to allow the coupling agent to bond with the surface of the nano-alumina; S24: After the reaction is completed, the mixture is filtered, the treated nano-alumina is collected, and dried at 70-90° C. to constant weight.

7. The method for preparing a wear-resistant engineering plastic masterbatch according to claim 4, characterized in that: The S3 specifically includes: S31: adding the degassed polyamide resin into a mixing device and heating it to 100-120° C. to maintain the fluidity of the polyamide resin; S32: while the polyamide resin is kept in a fluid state, polytetrafluoroethylene powder, pretreated nano-alumina and graphite powder are added in sequence to uniformly disperse the fillers; S33: After the filler is dispersed, the modified polyethylene is added and stirring is continued; S34: Raise the temperature of the mixing equipment to 120-140° C. and mix at a stirring speed of 200-300 rpm for 5-10 minutes until a uniform mixture A is formed.

8. The method for preparing a wear-resistant engineering plastic masterbatch according to claim 4, characterized in that: The S4 specifically includes: S41: gradually raising the temperature of the mixing device to 150° C., maintaining the stirring state, and ensuring that the previously formed mixture A is in a uniform flow state; S42: slowly adding epoxy resin into mixture A at 150° C. and continuously stirring for 5-8 minutes; S43: After the mixture is uniformly mixed, the temperature is further increased to 170° C.; S44: adding an antioxidant and a UV absorber at 170° C. and continuing stirring for 3-5 minutes to finally form a uniform mixture B.

9. The method for preparing a wear-resistant engineering plastic masterbatch according to claim 4, characterized in that: The S5 specifically includes: S51: preheating the temperature of the extrusion equipment to 170-190°C; S52: slowly adding the mixture B to the feeding port of the extruder, and controlling the feeding speed to 2-5 kg / hour; S53: performing composite extrusion treatment on the mixture B under the condition that the screw speed is set to 60-100 rpm; S54: During the extrusion process, the pressure in the extrusion equipment is controlled to be 5-8 MPa; S55: Cooling the extruded masterbatch matrix to 50-70° C. through a cooling device to stabilize its structural density and form a masterbatch matrix with a dense structure.

10. The method for preparing a wear-resistant engineering plastic masterbatch according to claim 4, characterized in that: The S6 specifically includes: S61: The extruded masterbatch matrix is ​​treated in a cooling water bath to be cooled to 30-50° C., so that the masterbatch matrix reaches a Shore hardness of D40-60; S62: sending the cooled masterbatch matrix into a pelletizer and cutting it into granules at a speed of 500-1000 kg / hour to obtain preliminary masterbatch after cooling and granulation; S63: dissolving the antistatic agent in ethanol or deionized water to prepare an antistatic coating solution with a mass concentration of 0.5%-2%, and stirring the solution evenly; S64: placing the preliminary masterbatch in a drum coating device, and spraying the antistatic coating solution evenly on the surface of the masterbatch in a rolling state; S65: Drying the masterbatch sprayed with the antistatic coating at 50-70° C. to a constant weight to form a final wear-resistant engineering plastic masterbatch product.

Citation Information

Cited By

  • High-performance scratch-resistant wear-resistant corrosion-resistant nylon material replacing steel with plastic

    CN120192653A